Rare Gastric Lesions Associated with Infection: A Histopathological Review - Mee Joo (Journal of Pathology and Translational Medicine, 2017)
Helicobacter pylori infection is associated with chronic gastritis, peptic ulcer disease, gastric adenocarcinoma, and mucosa-associated lymphoid tissue lymphoma. However, some rare gastric lesions exhibiting distinctive histological features may also be associated with H. pylori infection, including lymphocytic gastritis, granulomatous gastritis, Russell body gastritis, or crystal-storing histiocytosis. Although diverse factors can contribute to their development, there is convincing evidence that H. pylori infection may play a pathogenic role. These findings are mainly based on studies in patients with these lesions who exhibited clinical and histological improvements after H. pylori eradication therapy. Thus, H. pylori eradication therapy might be indicated in patients with no other underlying disease, particularly in countries with a high prevalence of H. pylori infection. This review describes the characteristic histological features of these rare lesions and evaluates the evidence regarding a causative role for H. pylori infection in their pathogenesis.